Structured image diagnosis of vertebral body degeneration and intervertebral disc damage - Binary image criteria and comparison for systematic image analysis for occupational diseases 2108 and 2110. Part 2: “Comparison images” - Braunschweig, Rainer; Kildal, Daniela; Meyer-Clement, Michael; Tiemann, Andreas; Janka, Rolf Matthias (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
BACKGROUND: Job-related limitations of earning capacity are eligible for recognition under social legislation and may be subject to compensation (see Part 1). METHOD: For the recognition of an occupational disease (BK), diagnostic imaging is required as part of the legal determination procedure for occupational diseases 2108/2110 ("occupational disc disease"). The focus is on image criteria on X-ray images and MRI examinations. In a consensus paper under the guidance of the German Social Accident Insurance Institutions from 2005, the characteristic patterns are defined and explained extensively and summarized in typical occupation-related constellations. This article presents representative image examples as a reference system for expert reporting as far as the typical patterns from the consensus paper are concerned. CONCLUSION: In Part 2, comparison images with the typical findings of the vertebral bodies and intervertebral discs according to occupational diseases are systematically presented, explained, and offered as a reference system for expert assessment. The image criteria can be used as "evidence by eye" (Heuck) in the recognition procedure. KEY POINTS: · Occupational diseases are defined by the legislator in the "List of Occupational Diseases".. · For occupational intervertebral disc diseases (OD nos. 2108/2110), constellations of findings are defined.. · Within the scope of diagnostic imaging, a large number of image criteria are used.. · Part 1 explains the basics and the legal background.. · Part 2 provides the image criteria on the basis of "comparison images" as a reference catalog.. CITATION FORMAT: · Braunschweig R, Kildal D, Meyer-Clement M et al. Structured image diagnosis of vertebral body degeneration and intervertebral disc damage - Binary image criteria and comparison for systematic image analysis for occupational diseases 2108 and 2110. Fortschr Röntgenstr 2024; 196: 912 - 920.
EVALuna2:568212